2021
DOI: 10.1136/bmjoq-2021-001413
|View full text |Cite
|
Sign up to set email alerts
|

Rationalising antibiotic use after low-risk vaginal deliveries in a hospital setting in India

Abstract: BackgroundIn 2017, a postoperative multidrug resistant case of urinary tract infection made obstetricians at Sitaram Bhartia Institute of Science and Research introspect the antibiotic usage in labouring mothers. Random case file reviews indicated overuse and variability of practice among care providers. This prompted us to explore ways to rationalise antibiotic use.MethodsA multidisciplinary team of obstetricians, paediatricians and quality officers was formed to run this improvement initiative at a private h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…In that study, the investigation was based on interviews with only 69 mothers, and no data were extracted from medical charts; therefore, the antibiotic prescription rate might have been underestimated. A study in India also revealed a high usage of antibiotics for low-risk vaginal deliveries (24-69%), and the decision of starting antibiotic was at the primary care provider's discretion and not based on any standard departmental protocol [16], which was similar to what was found in our study. In the uncomplicated vaginal delivery group, we also found that 62.1% of women in district hospitals received amoxicillin but 66.7% of women in health centers received ampicillin, and more women in health centers received antibiotics via the intramuscular route of administration.…”
Section: Discussionsupporting
confidence: 86%
“…In that study, the investigation was based on interviews with only 69 mothers, and no data were extracted from medical charts; therefore, the antibiotic prescription rate might have been underestimated. A study in India also revealed a high usage of antibiotics for low-risk vaginal deliveries (24-69%), and the decision of starting antibiotic was at the primary care provider's discretion and not based on any standard departmental protocol [16], which was similar to what was found in our study. In the uncomplicated vaginal delivery group, we also found that 62.1% of women in district hospitals received amoxicillin but 66.7% of women in health centers received ampicillin, and more women in health centers received antibiotics via the intramuscular route of administration.…”
Section: Discussionsupporting
confidence: 86%